Falling sensation in patients who undergo the Epley maneuver: A retrospective study - (:unkn) unknown (Medquest Communications LLC, 2005)
The author conducted a retrospective study to determine the prevalence of a falling sensation in patients who underwent the Epley canalith repositioning maneuver for the treatment of benign paroxysmal positional vertigo. The author studied a total of 436 maneuvers performed on 412 patients and observed 58 episodes (13%) of a strong falling sensation, some very severe. In almost every case, the sensation occurred when the patient was moved to the final (sitting) position; in 1 case, the sensation occurred nearly 30 minutes later. The author recommends that physicians who perform the Epley maneuver warn patients of the risk of a falling sensation, take steps to prevent its consequences, and monitor their patients for at least 30 minutes after the completion of the procedure.